Alcohol consumption among persons living with hypertension: evidence from a population-based study in Cape Verde - Joshua Okyere; Castro Ayebeng; Kwamena Sekyi Dickson (BMC Public Health)
Abstract Background Despite the well-documented effects of alcohol consumption on hypertension risk, there are persons living with hypertension who consume alcohol and may be at risk of alcohol use disorder (AUD). This paradox poses a critical public health concern and underscores a need to understand the alcohol consumption behavior of persons living with hypertension. This study investigates the prevalence and factors associated with alcohol consumption and AUD among persons living with hypertension in Cape Verde. Methods Using the 2020 WHO STEPS survey, we analyzed the observations of 1,136 adults in Cape Verde. Cross-tabulations, bivariable and multivariable logistic regression were performed in STATA version 18. The results from the multivariable logistic regression model were reported in their adjusted odds ratio (AOR) and corresponding 95% confidence interval (CI). Results Overall, 784 (69.1%) of the total sample reported consuming alcohol. The study revealed that 22.8% of those who consumed alcohol experienced AUD. Specifically, alcohol dependence symptoms were prevalent in 13.7% of participants who consumed alcohol in the last 12 months. Social/family problem and functional impairments were prevalent in 11.6% and 8.2%, respectively. Women were significantly less likely to consume alcohol [AOR = 0.17; 95% CI: 0.12–0.25] and experience AUD [AOR = 0.32; 95%CI: 0.20–0.51] compared to men. Additionally, individuals who consumed processed foods high in salt had more than twice the odds of consuming alcohol [AOR = 2.34; 95% CI: 1.62–3.39]. Urban residents [AOR = 1.76; 95% CI: 1.33–2.31] and current smokers [AOR = 2.23; 95% CI: 1.13–4.38] were more likely to consume alcohol. Individuals with higher education [AOR = 4.34; 95% CI: 1.97–9.55] were more likely to consume alcohol but less likely to experience AUD [AOR = 0.09, 95%CI: 0.02–1.87]. Conclusion The high prevalence of alcohol consumption and AUD among persons living with hypertension in Cape Verde signals a critical need for targeted public health strategies. Interventions should prioritize men, urban residents, current smokers, and individuals with higher education, given their higher likelihood of alcohol consumption. Additionally, given the lower likelihood of AUD among highly educated individuals, yet their higher alcohol consumption rates, interventions should balance education on the risks of excessive alcohol use while promoting responsible drinking.